Correlation between High Serum Uric Acid Levels with Occurrence of Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes Mellitus in Soetomo General Hospital - Deasy Putri Sukarno; Muhammad Hamdan; Fidiana Fidiana; Fadil Fadil; Mudjiani Basuki (Сахарный диабет)
Background: The increased serum uric acid (SUA) levels have been linked to macro vascular disease in Type 2 Diabetes Melitus. The correlation between serum uric acid levels and diabetic peripheral neuropathy has not been addressed properly. Objective: The aim of this study was to determine the correlation between high serum uric acid levels and diabetic peripheral neuropathy. Methods: This was a case-control design study and the sampling was done consecutively by following the inclusion and the exclusion criteria. The diabetic peripheral neuropathy was evaluated using Electroneuromyography (EMNG) and the serum were taken for uric acid level examination. Chi square test was used for the correlation analysis. Result: Thirty subjects were enrolled and divided into an experimental group of 15 subjects and a control group of 15 subjects as well. We found that the diabetic peripheral neuropathy did not show a significant correlation with high serum uric acid levels, p=0,136 and OR 3,143 (CI 95% 0,681-14,503). Conclusions: There was no correlation between high serum uric acid levels with diabetic peripheral neuropathy.